Political Implication of Islamic Dinar for the Stability in ASEAN-5 Region Post COVID-19 Crises - Harahap, Ali Musa (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
The paper analyses the possibility of monetary integration in ASEAN-5 countries, Indonesia, Malaysia, Philippines, Thailand, and Singapore for improving the stability in the region. The idea for regional monetary integration is grounded by the process of monetary union theory within the member states. In terms of volatility, by using certain assessment, the ASEAN-5 currencies are suggested to peg their national currencies into Dinar-Dirham Islamic exchange system since it empirically brings the lowest level of volatility, both during normal and crisis periods. Therefore, Dinar-Dirham could be proposed as the anchor currency for ASEAN-5 countries. The results statistically suggested that all ASEAN-5 countries could be grouped as eligible to employ Dinar-Dirham as their currencies.